Sharing the Ride: Ixodes scapularis Symbionts and Their Interactions - Stewart, Philip E.; Bloom, Marshall E. (Frontiers in Cellular and Infection Microbiology, 2020)
The deer tick Ixodes scapularis transmits a variety of disease agents in the United States, spreading the bacteria that causes Lyme borreliosis, the protozoan agent of babesiosis, and viruses such as Powassan. However, a variety of other organisms have also evolved symbiotic relationships with this tick species, and it seems likely that some of these microbes have simultaneously coevolved mechanisms to impact each other and their tick host. The number of organisms identified as I. scapularis symbionts has increased seemingly exponentially with the advent of PCR and next generation sequencing technologies, but convincing arguments have proposed that some of these are of environmental origin, unadapted to surviving the physiological conditions of the tick or that they are artifacts of ultrasensitive detection methods. In this review, we examine the diversity of the known microbes occurring within the I. scapularis microbiome, the evidence for interactions between microbes, and discuss whether some organisms reported to be symbionts of I. scapularis are experimental artifacts.